The global commodification of wastewater - Scott, Christopher A.; Raschid-Sally, Liqa (Informa UK Limited, 2012)
With growing scarcity and competition for water, urban wastewater is increasingly marketable because of its water and nutrient values. Commodification has implications for the current "residual? uses of wastewater (particularly by poor farmers in developing countries), for the risk of disease transmission, and for wastewater-dependent agro-ecosystems. Using examples from Pakistan, India, Ethiopia, Ghana, Mexico, and the United States, this paper contrasts commodification as it occurs in the developed and developing worlds and demonstrates the need for public information and coherent institutional frameworks, including private- and public-sector participation.